2019
DOI: 10.1029/2018ja026424
|View full text |Cite
|
Sign up to set email alerts
|

Interhemispheric Meridional Circulation During Sudden Stratospheric Warming

Abstract: Although sudden stratospheric warming (SSW) is mainly a northern high‐latitude phenomena, there are several reports of a concomitant global dynamical response throughout the mesosphere and lower thermosphere. Published reports based on model simulations so far attributed such variabilities to changes in global circulation; however, there is no clear explanation of how all these regions are physically connected during SSW events. The present investigation uses wind observations from two ground‐based specular me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 51 publications
(102 reference statements)
5
36
0
Order By: Relevance
“…Above this level, NAVGEM-HA vertical resolution degrades significantly, as the vertical grid spacing increases from ∼ 3 km near 80 km altitude to more than 5 km near 100 km altitude. To date, NAVGEM-HA winds and tides up to 90 km altitude have been shown to be in good agreement with both ground-based MR observations, as reported in McCormack et al (2017), Eckermann et al (2018) and Laskar et al (2019), and with independent satellite-based wind observations, as reported in Dhadly et al (2018). The present study extends these initial validation studies to include, for the first time, validation with two independent ground-based data sets over a 12-month period.…”
Section: Navgem-ha Meteorological Analysessupporting
confidence: 78%
“…Above this level, NAVGEM-HA vertical resolution degrades significantly, as the vertical grid spacing increases from ∼ 3 km near 80 km altitude to more than 5 km near 100 km altitude. To date, NAVGEM-HA winds and tides up to 90 km altitude have been shown to be in good agreement with both ground-based MR observations, as reported in McCormack et al (2017), Eckermann et al (2018) and Laskar et al (2019), and with independent satellite-based wind observations, as reported in Dhadly et al (2018). The present study extends these initial validation studies to include, for the first time, validation with two independent ground-based data sets over a 12-month period.…”
Section: Navgem-ha Meteorological Analysessupporting
confidence: 78%
“…For comparison with ground-based instruments, vertical profiles of NAVGEM-HA analyzed winds and temperatures are converted from the model vertical grid in geopotential altitude to a geometric altitude grid. To date, NAVGEM-HA winds and tides have been shown to be in good agreement with ground-based meteor radar observations (McCormack et al, 2017;Eckermann et al, 2018;Laskar et al, 2019;Stober et al, 2020) and with independent satellite-based wind observations as reported in Dhadly et al (2018). In the present study we employ NAVGEM-HA analyzed winds at 82.5 km altitude, staying below altitudes where effects of increased numerical diffusion imposed at the NAVGEM-HA upper boundary may impact the tides, to validate the method of extracting migrating tidal signatures from the SD meteor wind data.…”
Section: Navgem-hasupporting
confidence: 58%
“…NAVGEM-HA is a data assimilation and modeling system that extends from the surface to the lower thermosphere. In addition to standard operational meteorological observations in the troposphere and stratosphere, NAVGEM-HA assimilates satellite-based observations of temperature, ozone, and water vapor in the stratosphere, mesosphere, and lower thermosphere (McCormack et al, 2017). NAVGEM-HA output is on a 1 • latitude and longitude grid with a temporal frequency of 3 h, staying above the spatial and temporal Nyquist frequency of the tides studied in this work.…”
Section: Navgem-hamentioning
confidence: 99%
“…In 200 both studies mentioned above, it was confirmed that large-scale wave disturbances are the main driving force of the RMC due to the transfer of energy and angular momentum in the middle atmosphere and the MLT region. Laskar et al (2019) showed a significant weakening (up to a reversal) of both the mean and residual meridional circulation at the MLT heights during SSW observed in winters 2009/10 and 2012/13, leading to significant temperature fluctuations in the stratosphere of both hemispheres, which correspond our results discussed above.…”
Section: Residual Circulation At the Different Sw Stagessupporting
confidence: 88%